Rethinking Muhammadiyah: Masjid, Teologi Dakwah Dan Tauhid Sosial (Perspektif Filsafat Dakwah) - H. Abror, Robby (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2012)
As a dakwah movement that has a social ideals to bring the genuine Islamic community is the basic philosophical of Muhammadiyahâs movement. There are three important concepts such as, the movement of jamaâa, qaryah tayyibah and sakinah family. Then came the strategy of